Prosecutor’s Office of Ukraine Under Martial Law: Challenges, Trends. Statistical Data - Бакаянова, Нана Мезенівна; Бакаянова, Н. М.; Bakaianova, Nana M.; Khotynska-Nor, Oksana; Kravchenko, Maryna (Access to Justice in Eastern Europe, 2023)
Introduction of martial law on Ukraine’s territory on 24 February 2022, due to the full-scale invasion of the Russian Federation, affected the functioning of all institutions of state power without exception, including the field of justice. Its continuous functioning is a prerequisite for statehood and national security. This naturally led to a shift in the emphasis in scientific research, focusing on the problems that ensure the right to a fair trial. This emphasis that a person’s right to a fair trial is inviolable, even in conditions of martial law 5, led to emergence of studies which focus on a few problems, including organizing the work of courts in wartime6, advocacy’s functioning7,8 judgments’ enforcement9, and other related aspects. In this sense, the Prosecutor’s Office, as an integral element of justice administration, was undeservedly neglected. The study of the specificity of the Prosecutor’s Office’s work under martial law is isolated and eclectic in nature. For a long time in Ukraine, the Prosecutor’s Office was the object of discussions focused on the following issues: (a) its place in the system of public authorities10, (b) the list of functions11, (c) the system of Prosecutor’s Offices12, (d) requirements for the Prosecutor General13. However, the war created some adjustments. Like other state and public institutions, the entire prosecution system adapted to modern challenges associated with security problems, power outages, lack of mobile communication and Internet connection. The problems listed apply to Prosecutor’s Offices on all levels: the Office of the Prosecutor General, Regional Prosecutor’s Offices, district Prosecutor’s Offices, and the Specialized Anti-Corruption Prosecutor’s Office. Our study is based on the activity indicators of Kyiv, Odesa, Lviv, and Kharkiv Regional Prosecutor’s Offices, representing the northern, southern, western, and eastern regions of Ukraine, respectively. Considering the course of the war, different intensities of military aggression in various territories14, the regional (territorial) factor has a significant impact on the effectiveness of performance of the Prosecutor’s Office functions and specifies them. Therefore, such a sample will ensure the representativeness of the study’s results. We hope that these findings will be useful for everyone interested in the justice system’s functioning problems, in particular, the Prosecutor’s Office. After all, the Prosecutor’s Office of Ukraine is now gaining a unique experience of operating under the conditions of a full-scale war, which European countries do not have. Taking into account the global threats posed by the Russian Federation to the civilized world, study of the Prosecutor’s Office’s response to the extraordinary conditions of war will enable us to avoid destruction in the system of judicial protection of individual rights and freedoms in the future. The study is based on the systematic, statistical, historical, and comparative methods, as well as the method of selective analysis and synthesis of information, ensuring objectivity and complexity of the study. The authors used actual statistical and empirical data, particularly the materials of disciplinary practice, to properly argue their conclusions. Введення воєнного стану на території України 24 лютого 2022 року у зв’язку з повномасштабним вторгненням Російської Федерації вплинуло на функціонування всіх без винятку інститутів державної влади, включно зі сферою правосуддя. Його безперервне функціонування є передумовою державності та національної безпеки. Це закономірно призвело до зміщення акцентів у наукових дослідженнях, зосередившись на проблемах забезпечення права на справедливий суд. Цей наголос на тому, що право людини на справедливий суд є непорушним навіть в умовах воєнного стану 5, призвів до появи досліджень, які зосереджуються на кількох проблемах, зокрема організації роботи судів у воєнний час6, функціонуванні адвокатури7,8 виконання судових рішень9 та інших пов’язаних аспектах. У цьому сенсі прокуратура, як невід’ємний елемент здійснення правосуддя, була незаслужено знехтувана. Дослідження специфіки роботи прокуратури в умовах воєнного стану має поодинокий та еклектичний характер. Тривалий час в Україні прокуратура була об’єктом дискусій, зосереджених на таких питаннях: (а) її місце в системі органів державної влади10, (б) перелік функцій11, (в) система органів прокуратури12, (г) вимоги до Генерального прокурора13. Проте війна внесла певні корективи. Як і інші державні та громадські установи, вся система прокуратури адаптувалася до сучасних викликів, пов’язаних із проблемами безпеки, відключенням електроенергії, відсутністю мобільного зв’язку та Інтернету. Перераховані проблеми стосуються прокуратур усіх рівнів: Генеральної прокуратури, обласних прокуратур, районних прокуратур та САП. Наше дослідження ґрунтується на показниках діяльності Київської, Одеської, Львівської та Харківської обласних прокуратур, що представляють північний, південний, західний та східний регіони України відповідно. Враховуючи хід війни, різну інтенсивність військової агресії на різних територіях14, регіональний (територіальний) фактор має значний вплив на ефективність виконання функцій прокуратури та уточнює їх. Тому така вибірка забезпечить репрезентативність результатів дослідження. Сподіваємося, що ці висновки будуть корисними для всіх, хто цікавиться проблемами функціонування системи правосуддя, зокрема, прокуратури. Адже прокуратура України зараз отримує унікальний досвід роботи в умовах повномасштабної війни, якого немає у європейських країн. Враховуючи глобальні загрози цивілізованому світу з боку Російської Федерації, вивчення реагування прокуратури на надзвичайні воєнні умови дозволить у майбутньому уникнути руйнації в системі судового захисту прав і свобод особи. Дослідження базується на системному, статистичному, історичному та порівняльному методах, а також методі вибіркового аналізу та узагальнення інформації, що забезпечує об’єктивність та комплексність дослідження. Для коректної аргументації своїх висновків автори використали фактичні статистичні та емпіричні дані, зокрема матеріали дисциплінарної практики.
Khotynska-Nor O. Prosecutor’s Office of Ukraine Under Martial Law: Challenges, Trends. Statistical Data / O. Khotynska-Nor, N. Bakaianova, M. Kravchenko // Access to Justice in Eastern Europe 40-53. 2023. 3(20). P. 40-53. Режим доступу: https://doi.org/10.33327/AJEE-18-6.3-a000303
Keywords: Prosecutor’s Office; prosecutor; functions of the Prosecutor’s Office; war; Prosecutor’s Office in wartime; justice; Ukraine; Прокуратура; прокурор; функції прокуратури; війна; прокуратура у воєнний час; правосуддя; Україна